1999
DOI: 10.1017/s0021859699006504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and carpel size during pre-anthesis on potential grain weight in wheat

Abstract: The effect of environmental conditions immediately before anthesis on potential grain weight was investigated in wheat at the experimental field of the Faculty of Agronomy (University of Buenos Aires, Argentina) during 1995 and 1996. Plants of two cultivars of wheat were grown in two environments (two contrasting sowing dates) to provide different background temperature conditions. In these environments, transparent boxes were installed covering the spikes in order to increase spike temperature for a shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 25 publications
10
87
0
5
Order By: Relevance
“…The IGW was positively associated with grain filling rate across all source-sink treatments, which is consistent with previous studies where grain weight has been found to be closely related with the grain filling rate (Chowdhury and Wardlaw, 1978;Calderini et al, 1999;Sandaña et al, 2009;Serrago et al, 2013). Nevertheless, no association was found between IGW and grain filling duration; however, the source-sink treatments reduced (p ≤ 0.001) grain filling and in turn decreased cumulative intercepted radiation available for plants.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The IGW was positively associated with grain filling rate across all source-sink treatments, which is consistent with previous studies where grain weight has been found to be closely related with the grain filling rate (Chowdhury and Wardlaw, 1978;Calderini et al, 1999;Sandaña et al, 2009;Serrago et al, 2013). Nevertheless, no association was found between IGW and grain filling duration; however, the source-sink treatments reduced (p ≤ 0.001) grain filling and in turn decreased cumulative intercepted radiation available for plants.…”
Section: Discussionsupporting
confidence: 90%
“…IGW was calculated using a bilinear model (0.80 ≥ r 2 ≥ 0.99) subjected to boundary conditions (i.e. GW is described by two equations with one break point) as in Calderini et al (1999). Grain filling durations (GFD in °C d and days) were calculated from the break point, which is the time from At-PM, and grain filling rate (mg °C d -1 , GFR) was estimated from the regression slopes (Miralles et al, 1996).…”
Section: Manipulation and Calculation Of The Source-sink Ratiomentioning
confidence: 99%
“…It has been found that the growth period immediately before anthesis, which coincides with rapid spike growth, determines floret fertility and in turn grain number at maturity (González et al, 2011;Slafer and Rawson, 1994). This critical period also overlaps with the ovary development within florets, and consequently affects individual grain weight (Calderini et al, 1999). Immediately after fertilization, endosperm cell division and enlargement take place (Shewry et al, 2012), an important process determining final individual grain weight (Brocklehurst, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall and air temperature are among the most investigated meteorological variables in climatic trend studies, mainly due to the serious implications that their spatial and temporal changes can have on several environmental and socioeconomic aspects [1][2][3]. With regard to the temporal distribution of rainfall, long-term trends have been detected in several areas of the world [4,5].…”
Section: Introductionmentioning
confidence: 99%